Pengaruh Penambahan Gula Kelapa Pasta pada Ensilase Ikan Rucah Terhadap Kualitas Silase - Rimbawanto, Efka Aris; Yusiati, Lies Mira; Baliarti, Endang; Utomo, Ristianto (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2015)
The objective of this research was to analyze the effect of coconut sugar paste in naturally fermented trash fish ensilage on chemical change. Grinded trash fish (Pomadasys macullatus) was mixed with coconut sugar paste (0, 15, 30 and 45%/kg fresh trash fish) without inoculation in plastic bag. Anaerobe incubation was conducted at room temperature (29°±1°C). Chemical change (pH, lactic acid, ammonia, non-protein nitrogen, peroxide value and free fatty acid) was observed during fermentation period of 0, 4, 8, 12, 20 and 24 days. The experiment which had a completely randomized design to select the best amount of coconut sugar paste and fermentation period in trash fish ensilage. Fresh trash fish and fermentation product (trash fish silage) determined by the proximate analysis (dry matter, ash, crude protein and crude fat). Result indicated that the pH decreased remained constan at 4,4 after 16-day fermentation. Lactic acid, ammonia, non-protein nitrogen, peroxide value and free fatty acid during fermentation significantly increased due to different levels of coconut sugar paste and fe rmentation period. Conclusively, coconut sugar paste at the level of 15%/kg fresh trash fish was the best combination in natural fermentation with 16-day fermentation period and the product was potential protein source (45% DM) for animal feed. Key word: Trash fish, coconut sugar paste, silage, fermentation.